PENDIDIKAN AGAMA KRISTEN DI TENGAH ARUS POST-MODERN: ESKATOLOGI SEBAGAI FONDASI PEMBENTUKAN KARAKTER - Beni; Monika Kabe'; Marla Epiphania Payung; Yohanis Medi; Elsia (CV. Adiba Aisha Amira, 2026)
Christian Religious Education (CRE) faces complex challenges in the post-modern era characterized by relativism of truth and spiritual identity crisis. This research explores the integration of eschatological understanding in Christian character formation through qualitative methods with a library research approach. Findings indicate that balanced eschatological understanding positively correlates with spiritual vigilance, moral integrity, psychological resilience, and mission engagement. However, contemporary CRE practices reveal critical gaps: fragmentation of eschatological content, dominance of cognitive-doctrinal approaches, and limited educator competence. The research proposes a holistic integration model that positions eschatology as a theological framework integrating the entire curriculum and adopts transformative pedagogy balancing cognitive, affective, and praxis dimensions. This model is designed to address sensationalist eschatological distortions, develop